Cardiac Amyloidosis: Multi-modal Imaging of Disease Activity and Response to Treatment - Patel, Rishi K (Circ Cardiovasc Imaging, 2021)
Cardiac amyloidosis (CA) is a disease characterized by the deposition of misfolded protein deposits in the myocardial interstitium. While advanced CA confers significant morbidity and mortality, the magnitude of deposition and ensuing clinical manifestations vary greatly. Thus, an improved understanding of disease pathogenesis at both cellular and functional levels would afford critical insights that may improve outcomes. This review will summarize contemporary therapies for the two major types of CA, transthyretin (ATTR) and light-chain (AL) amyloidosis, and outline the capacity of imaging modalities to both diagnose CA, inform prognosis, and follow response to available therapies. We explore the current landscape of echocardiography, cardiac magnetic resonance, and bone scintigraphy in the assessment of functional and cellular parameters of dysfunction in CA throughout disease pathogenesis. Finally, we examine the impact of concurrent advances in both therapeutics and imaging on future research questions that improve our understanding of underlying disease mechanisms. Multi-modal imaging in CA affords an indispensable tool to offer individualized treatment plans and improve outcomes in patients with CA.